Ocular metastases profile in a tertiary hospital in São Paulo, Brazil - Matheus Senna Pereira Ogata; Guilherme Rodrigues Ferreira; Melina Correia Morales; Arthur Gustavo Fernandes (International Journal of Retina and Vitreous, 2024)
Abstract Objective Ocular metastases are the most common intraocular tumours in adults. Data regarding the occurrence of these tumours in the Brazilian population is scarce. We aimed to investigate the profile of ocular metastases of patients referred to tertiary hospital service in São Paulo, Brazil. Design Retrospective study. Participants Patients referred to the Ocular Oncology service of the Federal University of São Paulo with initial diagnostic hypothesis of ocular metastasis. Methods Data was retrospectively collected from medical records from June 2017 to June 2023. Age, sex, primary tumour site, previous knowledge of the systemic diagnosis, laterality, initial visual acuity (VA), local or systemic treatment and mean follow-up period were obtained. Results A total of 37 cases were referred to the ocular oncology division due to a suspected ocular metastasis, 15 (40.5%) were confirmed. Mean age at diagnosis was 53.47 ± 16.01 years old, the majority (86.7%) of patients already knew the systemic diagnosis. Breast cancer (66.7%) was the most common primary site, followed by Lung cancer (26.7%). Both eyes were affected in 66.67% of the cases, all patients had metastases at the choroid (100.0%), and the mean initial VA was 1.37 ± 1.04 logMAR. Chemotherapy was the main systemic treatment modality (73.3%), and most patients had no ocular treatment (53.3%). The mortality rate along the follow-up period was 30.0%. Conclusions Considering the number of new patients absorbed by the Ocular Oncology service over the study period, the frequency of ocular metastases was relatively low. The patients’ characteristics was comparable to data published in the international literature.